Experimental and Theoretical Insights into the Structural Disorder and Gas Sensing Properties of ZnO - Lima, Bruno Sanches de; Martinez-Alanis, Paulina R.; Guell, Frank; Santos Silva, Weverton Alison dos; Bernardi, Maria I. B.; Marana, Naiara L. [UNESP]; Longo, Elson; Sambrano, Julio R. [UNESP]; Mastelaro, Valmor R. (Amer Chemical Soc, 2021)
Recently, it was demonstrated that ZnO thin films sputtered under oxygen-rich atmospheres exhibit localized structural disorder with a significant impact on their physical properties due to the presence of high energetic ions in the plasma. Here, highly disordered ZnO thin films have been realized simply by using a metallic Zn target under a deposition atmosphere of pure oxygen (O-2). The results of XRD and Raman spectroscopy show that the defects induced during the deposition crystallize a highly disordered wurtzite-type structure. In addition, theoretical DFT calculations were applied for a better comprehension of the nature of these structural defects, in which it is shown that the presence of Zn and O in interstitial positions may be responsible for a symmetry break in the wurtzite structure. It is shown that high disorder of the structure has a significant impact on its fundamental properties. For instance, the UV-vis absorption curve shows a significant increase in the bandgap of ZnO, while photoluminescence (PL) measurements show the emergence of bands in the visible range, confirming the presence of Zn and O in interstitial positions. This manuscript also explores the gas sensing properties of films deposited under a pure oxygen atmosphere. Our results demonstrate that their sensitivity can be significantly enhanced toward oxidizing gas detection, such as ozone. On the other hand, it is shown that the gas sensing properties regarding reducing gas detection, such as H-2, are not significantly altered when compared to non-disordered ZnO.
Keywords: ZnO; structural disorder; RF magnetron sputtering; reactive atmosphere; gas sensor